If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2u = -12.4 Solving -2u = -12.4 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Divide each side by '-2'. u = 6.2 Simplifying u = 6.2
| 2a^2b(-3ab^2)= | | x-5/4=-4 | | -20=2(4+7n) | | 9(z-1)-2(3z)+4=7 | | 34-5(x-3)=119 | | 34-5(x-3)=37 | | 19-3(x+4)+5x=11 | | 6x+2x=80 | | (-3x)-(-13)=15 | | -16=2(m-3) | | 3(2x-4)+5(x+1)=37 | | 2(x-3)+8x=76 | | -2x-2=2 | | -7(7-x)=-21 | | -5(v+4)+2v+7=8v+11 | | 18-5x-8=-24 | | -16=4(p+4) | | -4a+45=17 | | 10x+20=22 | | -3x-2=10 | | 5x+3(x-4)=28 | | -15=12-2n+5n | | -2(-3+n)-3n=-24 | | 3z-5z=12 | | 8x+22=3x-8 | | -6(v+4)+2v+7=8v+9 | | 4.4m-1.2=9.8 | | -7(v+2)+4v+7=8v+7 | | 7(7x+1)-4x=13(3x-2) | | 4(2+5)2-52= | | -3i*6i-3(-7+6i)= | | x^2+2x+4=y |